Building Coalitions: Introduction - Daney Jackson; William Maddy; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY493, Part 1 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.